Evaluation of the in vivo subacute toxicity of Otolith as a novel traditional hypoglycemic agent - Abdullah Ahmed Areqi; Doaa Anwar Ibrahim
In coastal areas like Hodeida governorate-Yemen, otolith, or "ear stone", are used to treat diabetes. Locals believe that these formations can manage diabetes and relieve migraine pain. This study examines the in vivo subacute toxicity and safety of catfish otolith as a novel traditional antidiabetic agent. Twenty \ fourmale rats were evenly divided into four six-rat groups. Control group (Group 1) received 0.9% w/v sodium chloride for 21 days. The remaining three groups received oral otolith at different doses for the same time. Group 2, the low-dose group, received 5 g/day otolith per body weight. Mid-dose group 3 received 10 g/day otolith per body weight. Finally, Group 4, the high-dose group, received 15 g/day otolith per body weight. The animals' behavior and anomalies were recorded throughout the experiment. Biochemical tests like liver and kidney function and hematological tests like total blood count were done at the end of the experiment. In large doses, otoliths reduced cholesterol, LDL, and triglycerides and increased HDL. Otolith did not affect renal function or electrolyte balance at the tested doses. It affected certain hepatic enzyme functions at higher doses, but protein levels remained stable across doses, indicating neither liver injury nor considerable hepatic function loss. This study sheds light on otolith's safety, notably for renal function, electrolyte homeostasis, and liver health.